Making Use of Critical Management Theory: A Discursive Intervention for Employee Empowerment - Ritchie, Leah; Jain, Anurag; Kelkar, Mayuresh (Journal of Marketing Development and Competitiveness, 2019)
Critical management scholars have examined employee oppression (i.e., wage inequity, union busting, marginalization and silencing), by leveling criticism against traditional management practices, arguing for more pluralistic relationships across agencies. Despite this action-oriented charge, the field is currently lacking in its potential to provide employees tools they need to create a more equitable balance of power in the workplace. To address this gap, this paper describes an organizational intervention that can be used by employees to openly discuss and take action to remedy the problem of power inequity. The paper also includes a discussion of ethical constraints related to the intervention.